Analysis of Local Economic Potential and Economic Competitiveness in Surabaya City - Yusuf Hariyoko; Anggraeny Puspaningtyas (Indonesian Association for Public Administration (IAPA), 2019)
Abstract Law Number 23 of 2014 concerning Regional Government clause 29 verse 5 explains that